Lattice-Based Cryptography in the Quantum Era: A Survey - Cisneros, Mauricio (2023)
The advent of quantum computing reveals current classical cryptography’s incapacity to withstand attacks within the new paradigm. Quantum algorithms break such encryption with impressive ease, with Shor and Grover algorithms being the main perpetrators. Lattice-based key encryption is the suggested solution in multiple instances, as the complexity and randomness that these methods add to message encryption make them one of the best short- and medium-term solutions. In 2016, NIST launched a contest to find algorithms to incorporate into its security standard. Four algorithms from the third round were selected to be standardized, including the lattice-based CRYSTALSkyber. Of the latter, variants have been and are still being developed that manage to amend some weaknesses found in its implementation, such as side-channel attacks or performance issues. This investigation discusses different publications on lattice-based cryptography in conjunction with cryptanalysis in the quantum era.